Finite element analysis of mechanical response of fracture fixation functionally graded bone plate at paediatric femur bone fracture site under compressive and torsional loadings. (2021) - Kanu, Nand Jee; Patwardhan, Devendra; Gupta, Eva; Vates, Umesh Kumar; Singh, Gyanendra Kumar
Abstract: The previous investigations clearly demonstrated that nearly 25% of the paediatric injuries are due to fracture of bones. Children are more prone to paediatric injuries due to their childish behaviour. Their bones are subjected to axial compressive stresses due to their weight as well as torsional and bending stresses with maximum values at fracture sites of paediatric femur (PF) bones. The present investigation compares commercially available fracture fixation (FF) bone plate made up of titanium alloy with newly developed functionally graded (FG) prosthetic bone plate (graded stepwise in thickness direction using isotropic hydroxyapatite (Ha) and titanium (Ti) materials) for the treatment of fractured paediatric femur bones. The static stress analyses are carried out using finite element method (FEM) for the children under age group of 0 – 3 years . Furthermore, the combined compressive and torsional stresses are evaluated at 1%, 50%, and 75% healing stages of PF bones at their fracture sites using non-contacted bone-plate assemblies. The results favor the layered FG fracture fixation bone plates as they shield the PF bones from equivalent (von Mises) stresses as compared to the widely used FF bone plate made up of titanium alloy by (a) around 75 – 85% under each loading, i.e., either compressive or torsional loading at a time in the contacted cortical PF bone-FF plate systems; and (b) around 0.5 to 4 – 4.5% under each loading, i.e., either compressive or combined (both compressive and torsional loads) loading at a time in the non-contacted cortical PF bone-FF plate systems.